2004
DOI: 10.1038/sj.npp.1300512
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of N-acetyl-L-cysteine on the Reduction of Dopamine Transporters in the Striatum of Monkeys Treated with Methamphetamine

Abstract: Several lines of evidence suggest that oxidative stress might contribute to neurotoxicity in the dopaminergic nerve terminals after administration of methamphetamine (MAP). We undertook the present study to determine whether intravenous administration of N-acetyl-L-cysteine (NAC), a potent antioxidant drug, could attenuate the reduction of dopamine transporter (DAT) in the striatum of monkey brain after administration of MAP. Positron emission tomography studies demonstrated that repeated administration of MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 35 publications
(43 reference statements)
3
36
0
Order By: Relevance
“…Indeed, DA depleting METH treatments induce ROS (Pubill et al,2005), ROS promote Nrf2 induction of detoxifying enzymes, and treatment with antioxidants attenuate methamphetamine toxicity (Hashimoto et al,2004;McCann and Ricaurte,2004). Also, Nrf2 KO have been shown to be hypersensitive to in vivo neurotoxicity induced by other oxidative stressors, such as the mitochondrial complex II inhibitor 3-nitropropionic acid or tertbutylhydroquinone (Calkins et al,2005;Chanas et al,2002;Shih et al,2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, DA depleting METH treatments induce ROS (Pubill et al,2005), ROS promote Nrf2 induction of detoxifying enzymes, and treatment with antioxidants attenuate methamphetamine toxicity (Hashimoto et al,2004;McCann and Ricaurte,2004). Also, Nrf2 KO have been shown to be hypersensitive to in vivo neurotoxicity induced by other oxidative stressors, such as the mitochondrial complex II inhibitor 3-nitropropionic acid or tertbutylhydroquinone (Calkins et al,2005;Chanas et al,2002;Shih et al,2005).…”
Section: Discussionmentioning
confidence: 99%
“…3) Nrf2 KO will be more susceptible to methamphetamine(METH)-induced neurotoxicity. This latter hypothesis was based on evidence that METH-induced toxicity to dopamine (DA) terminals results, at least in part, from the induction of reactive oxygen species (ROS), such as superoxides and free hydroxyradicals (Pubill et al,2005), that ROS promote Nrf2 induction of detoxifying enzymes (Kita et al,2003), and that treatment with antioxidants attenuates METH toxicity (Hashimoto et al,2004). Figure 1A shows that in ventral striatal slices (containing nucleus accumbens), homozygous Nrf2 deletion did not alter system xc-basal activity as measured by Na + -independent L-[ 3 H]-glutamate uptake in pmoles/mg protein/minute.…”
Section: Introductionmentioning
confidence: 99%
“…One study has demonstrated that a high concentration of fluphenazine can reduce dopamine uptake by rat striatal synaptosomes in vitro (Westfall et al 1976). In addition to these putative mechanisms, literature data have shown that oxidative stress decreases the activity of dopamine transporters (Huang et al 2003;Hashimoto et al 2004). In view of the antioxidant property of diphenyl diselenide, we have also investigated the role of oxidative stress in fluphenazineinduced VCMs.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is currently no pharmacological treatment for the wide range of signs associated with METH exposure (Hashimoto 2007;Chen et al 2010). Repeated administration of METH is known to induce dopaminergic neurotoxicity in rodents and non-human primates, by producing long-term depletion of dopamine (DA) and its metabolite, 3,4-dihydroxyphenylacetic acid (DOPAC), as well as reducing the density of DA transporter (DAT) in the striatum (Davidson et al 2001;Cadet et al 2003;Fukami et al 2004;Koike et al 2005;Zhang et al 2006;Hashimoto et al 2004;2007;Hagiwara et al 2009). Furthermore, it has been reported that levels of dopamine nerve terminal markers, DA, tyrosine hydroxylase, and DAT are decreased in the striatum of post mortem brains (nucleus accumbens, caudate, putamen) of chronic METH users (Wilson et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lines of evidence implicate oxidative stress in the METH-induced behavioral and neuropathological changes that damage brain dopaminergic neurons (Açikgöz et al 2001;Fukami et al 2004;Miyazaki et al 2006;Hashimoto et al 2004Hashimoto et al , 2007Cadet et al 2007;Yamamoto and Raudensky 2008;Chen et al 2010). The potent antioxidant sulforaphane (SFN: 1-isothiocyanato-4-methylsulfinylbutane) is an organosulfur compound derived from a glucosinolate precursor found in cruciferous vegetables such as broccoli, Brussels sprouts, and cabbage (Zhang et al 2005;Juge et al 2007).…”
Section: Introductionmentioning
confidence: 99%